Late-onset dynamic outflow tract gradient in the setting of tako-tsubo cardiomyopathy: An interesting phenomenon with potential implications? - Yalta, Kenan (Indian Heart J, 2017)
In clinical practice, dynamic left ventricular outflow tract obstruction (LVOTO) in the setting of tako-tsubo cardiomyopathy (TTC) has been regarded as an early-onset complication typically emerging in accordance with wall motion abnormalities. However, dynamic LVOTO has, very rarely, been reported as a late-onset phenomenon in the setting of TTC as well (arising in the late stage or after recovery). Accordingly, the present paper aims to highlight clinical relevance and potential implications of late-onset LVOTO in the setting of TTC.